Implementation Of E-Procurement Agreement Between Indonesian and Malaysia - Nur assyafaah, Nur assyafaah; Dompak, Timbul (JPAP: Jurnal Penelitian Administrasi Publik, 2024)
This research compares e-procurement applications in Indonesia and Malaysia, which are the applications of e-procurement as a renewal of the goods/services procurement system. Malaysia and Indonesia have implemented e-procurement, and the presence of corrupt practices has made both countries focus on increasing transparency. The number of procurement transactions in Indonesia increased significantly from 2008 to 2017, with total spending reaching more than 1000 trillion Rupiah in 2020. The number of online e-procurement transactions in Malaysia has decreased from 2014-2015, with an overall decrease in transactions from 1,577,740 to 1,540,314. The results showed that Malaysia and Indonesia conducted Peer Exchange activities to exchange experiences and knowledge about Ecolabeling and GPP. Green procurement can use e-procurement as one of the methods to ensure transparency and efficiency in the procurement process. E-procurement can help control inventory, reduce costs, and improve agreement conformity with suppliers. Therefore, the author would like to compare the implementation of the system in Indonesia and Malaysia in terms of the procurement of goods/services.